The structure of Singapore's financial system. - Teo, Hong Poey. (2008)
This paper seeks to evaluate the structure of Singapore’s dichotomised financial system and the viability of its framework in today’s economic circumstances. A study on the attractiveness of the system as a destination for financial capital flows is also undertaken.